Research and Development in Intelligent Systems XXI Proceedings of AI-2004, the Twenty-fourth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence - Coenen, Frans; Allen, Tony (Springer London : Imprint: Springer, 2005)
RESEARCH AND DEVELOPMENT IN INTELLIGENT SYSTEMS XXI The papers in this volume are the refereed technical papers presented at AI-2004, the Twenty-fourth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence, held in Cambridge in December 2004. The papers in this volume present new and innovative developments in the field, divided into sections on AI Techniques I and II, CBR and Recommender Systems, Ontologies, Intelligent Agents and Scheduling Systems, Knowledge Discovery in Data and Spatial Reasoning, Image Recognition and Hypercubes. This is the twenty-first volume in the Research and Development series. The series is essential reading for those who wish to keep up to date with developments in this important field. The Application Stream papers are published as a companion volume under the title Applications and Innovations in Intelligent Systems XII.